Obstetrics outcomes of pregnancy with uterine fibroids in tertiary care hospital - Asima Afzal; Samina Ashraf; Waseeqa Nigeen (Barpeta Obstetrics and Gynaecological Society, 2021)
Aim: To determine the clinical profile and obstetric outcomes among the pregnant women with uterine fibroids. Methods: This prospective observational study was carried out over a period of 1 ½ years from July 2018 to Jan 2020.96 pregnant patients with uterine fibroids were included in the study. Various parameters like maternal age, parity, number and size of fibroids, obstetric complications and mode of delivery were noted. Complete clinical examination and routine investigations were performed at each antenatal visit. Ultrasonograpy was done during each visit for fetal assessment and to observe the change in the size of the fibroid. Results: Out of 96 patients recruited, 85 of them completed the study. The mean age of patients was 32.56±4.3 years, primigravida was 27.05%, multigravida was 72.94%. Spontaneous conception was seen in75.29% and 24.70% used assisted reproductive treatment for conception. Spontaneous abortion was seen in 11.76%, premature delivery in 18.7%, and full term delivery in 81.3%. Caesarean section was performed in 74.67%of cases and normal vaginal delivery in 25.33%. 12.9% had threatened miscarriage, 18.7% had preterm labour, 5.3% had antepartum bleeding due to placenta previa, 11(14.67%) had postpartum haemorrhage.Intramural location and multiple fibroids were associated with increased risk of caesarian section as compared to sub serosal fibroids and single fibroids. Conclusions: Uterine fibroids in pregnancy are associated with higher risk of adverse obstetric complications. Regular check up is advised during antenatal period to detect any adverse obstetric complications, which will help to improve the outcome.